Progressive Bone Destruction in Rapidly Destructive Coxopathy Is Characterized by Elevated Serum Levels of Matrix Metalloprotease-3 and C-Reactive Protein. Issue 1 (January 2022) - Ando, Wataru; Hashimoto, Yoshichika; Yasui, Hirohiko; Ogawa, Takeshi; Koyama, Tsuyoshi; Tsuda, Takayuki; Ohzono, Kenji
Abstract : Objective: Rapidly destructive coxopathy (RDC) is a rare condition characterized by rapid joint space narrowing; however, its pathology remains unclear. This study aimed to clarify the association of laboratory biomarkers with the radiological progression of RDC. Methods: We examined 34 female and 4 male patients with RDC between October 2010 and April 2018. Patients were divided into 3 groups according to the progressive radiographic staging of RDC. Group 1 patients had progressive obliteration of the joint space without subchondral destruction (n = 11), group 2 had progressed subchondral destruction (n = 18), and group 3 had cessation of bone destruction observed for more than 6 months (n = 9). Clinical evaluation results were assessed using the Japanese Orthopedic Association hip score. Blood test results, including serum matrix metalloproteinase-3 (MMP-3), and C-reactive protein (CRP), were also evaluated. Results: There were no significant differences in patient background or Japanese Orthopedic Association hip scores among the groups. However, there were significant differences in MMP-3 levels among groups, with MMP-3 levels in group 2 being significantly higher than those in group 3 (group 2, 118.4 ± 81.2 ng/mL; group 3, 42.5 ± 15.1 ng/mL, p < 0.001). The CRP levels in group 2 were also significantly higher than those in group 3 (group 2, 0.77 ± 0.92 mg/dL; group 3, 0.13 ± 0.07 mg/dL, p = 0.019), but elevated CRP levels in group 2 decreased back to the reference range. Conclusions: Matrix metalloproteinase-3 and CRP are the biomarkers of RDC progression but not of its occurrence. Severe inflammatory response may be associated with bone destruction in RDC.